1983
DOI: 10.1128/aac.23.6.944
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of cefonicid for treatment of skin infections

Abstract: Twenty patients with skin and soft-tissue infections were treated with parenteral cefonicid. Cultures obtained in cellulitis cases from an aspirate of a leading edge of inflammation were positive in 42% of these patients. Pathogens isolated were Staphylococcus aureus (six strains), Proteus mirabilis (one strain), and Streptococcus agalactiae. Adverse effects were pain on intramuscular injection (two patients), rash (one patient), and positive Coombs test (one patient). All side effects were mild and none requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…12,14,15,18,25 In our study, a bactériologie diagnosis was made in only 4 (15%) (confidence interval, 4% to 36%) of 26 needle aspiration cultures of cellulitis. This yield is particularly low when considering that the study population was hospitalized due to the severity of their infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,14,15,18,25 In our study, a bactériologie diagnosis was made in only 4 (15%) (confidence interval, 4% to 36%) of 26 needle aspiration cultures of cellulitis. This yield is particularly low when considering that the study population was hospitalized due to the severity of their infection.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies were done retrospectively,6,7,14 whereas other studies used a prospective method.13,18 Most studies did not discriminate between purulent soft-tissue infections and the nonpurulent superficial inflammation of cellulitis.2,3,6,1012, 14,15,18 Those studies that defined cellulitis as a nonpurulent process that occurred without disruption of cutaneous integrity dem¬ onstrated singularly poor results with the use of needle aspi¬ ration cultures to isolate putative pathogens.2,7 Age is another confounding variable in these studies, as several did not discriminate between patients aged 18 years or older and those younger than 18 years.6,7,10 The efficacy of needle aspira¬ tion in the pediatrie age group consistently demonstrates that this technique yields a pathogen with much greater frequen¬ cy.13,18,27 It has also been suggested that patients with comor¬ bid disease have an increased likelihood of positive needle aspiration cultures,28 yet most studies did not distinguish such patients.…”
Section: Resultsmentioning
confidence: 99%
“…Pathogen identification can be obtained via direct needle aspiration of the cellulitis, which may be superior to blood culture, although this method was rarely used among our study population. Needle aspiration has demonstrated variable yield (10%-60%), [24][25][26][27][28][29][30] and studies of this method are limited to the era of Haemophilus influenzae type b, prior to the rise in CA-MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, other organisms have been isolated from patients with cellulitis, including S. aureus and other Gram-positive organisms, as well as Gram-negative organisms. 7,8 Cellulitis due to E. coli seems to be rare. To our knowledge, four cases in adults have been reported in the English language literature.…”
Section: Discussionmentioning
confidence: 99%